2020
DOI: 10.3390/cancers12010193
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin VI Induces Caspase-1-Mediated Pyroptosis via the Induction of ROS/NF-κB/NLRP3/GSDMD Signal Axis in Non-Small Cell Lung Cancer

Abstract: Trillium tschonoskii Maxim (TTM), a traditional Chinese medicine, has been demonstrated to have a potent anti-tumor effect. Recently, polyphyllin VI (PPVI), a main saponin isolated from TTM, was reported by us to significantly suppress the proliferation of non-small cell lung cancer (NSCLC) via the induction of apoptosis and autophagy in vitro and in vivo. In this study, we further found that the NLRP3 inflammasome was activated in PPVI administrated A549-bearing athymic nude mice. As is known to us, pyroptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(171 citation statements)
references
References 83 publications
(103 reference statements)
5
166
0
Order By: Relevance
“…As a critical form of cell death, pyroptosis has been reported to be involved in many physiological processes, such as regulation of tumor immune microenvironment [35], treatment of acute myeloid leukemia [36] and act as an innate immune effector against intracellular bacteria [37]. There are various researches showing an association between pyroptosis and tumor proliferation [38][39][40]. In this study, we found that tanshinone II A enhanced cell proliferation and inhibited apoptosis by up-regulating GSDMD expression on HeLa cells, especially at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As a critical form of cell death, pyroptosis has been reported to be involved in many physiological processes, such as regulation of tumor immune microenvironment [35], treatment of acute myeloid leukemia [36] and act as an innate immune effector against intracellular bacteria [37]. There are various researches showing an association between pyroptosis and tumor proliferation [38][39][40]. In this study, we found that tanshinone II A enhanced cell proliferation and inhibited apoptosis by up-regulating GSDMD expression on HeLa cells, especially at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…ROS play a crucial role in tumorigenesis, with accumulating evidence suggesting that excessive production of ROS directly causes DNA damage and leads to apoptosis. 38,39 Consequently, targeting ROS has been considered a promising strategy for anti-tumor therapy, since it can stimulate or inhibit different cell signaling pathways to induce apoptosis and autophagy thereby inhibit tumor growth. 40,41 Additionally, high levels of ROS can induce cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Caspase-1 promotes the secretion of IL-1β, IL-18 and GSDMD, consequently leading to the impairments of neuroplasticity ( Qi et al, 2018 ; Shao et al, 2018 ). ROS is a crucial activator in triggering NLRP3 inflammasome activation directly or indirectly by acting on NF-κB ( Teng et al, 2020 ). SIRT3, a NAD+-dependent deacetylase that mainly located in mitochondria, modulates signal pathways to control ROS generation ( Teng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ROS is a crucial activator in triggering NLRP3 inflammasome activation directly or indirectly by acting on NF-κB ( Teng et al, 2020 ). SIRT3, a NAD+-dependent deacetylase that mainly located in mitochondria, modulates signal pathways to control ROS generation ( Teng et al, 2020 ). SIRT3 maintains the ROS homeostasis by targeting mitochondrial enzymes such as superoxide dismutase 2 (SOD2), which transforms harmful superoxide radicals into nontoxic oxygen or hydrogen peroxide ( Zheng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%